DESIGN AND IMPLEMENTATION OF A PROTOTYPE AUTOMATED FOR THE PROCESSING OF PASTES AND LIQUIDS - Ruiz Lizama, Edgar (2007)
The article focused the next problem: What physical and virtual instruments interact in an interface Human Machine in order to automate a prototype to the process of pastes and liquids?; the design includes the measured and the selection of devices. The implementation considers the SMAR'S SYSTEM 302 platform to the process supervision and control; As a result of this we have an automated module whose investment was returned by the CEMA's courses.